Fourth Toeplitz Determinants for Starlike Functions Defined by Using the Sine Function. (30th August 2021) - Zhang, Hai-Yan; Tang, Huo
Abstract : In this article, we aim to study the upper bounds of the fourth Toeplitz determinant T 4 2 for the function class S s ∗, which are connected with the sine function.